BMJ Awards 2021: Respiratory team of the year. (16th September 2021) - Limb, Matthew
Abstract : Perhaps unsurprisingly, three of the shortlisted respiratory teams have innovated in response to the covid-19 pandemic, but there is also work on managing tracheostomies and tuberculosis. Matthew Limb reports